2018
DOI: 10.15587/1729-4061.2018.126372
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the mechanism that forms breadbaking properties of the spelt grain

Abstract: Теоретично обґрунтовано та експе-риментально підтверджено техноло-гічні властивості зерна 16 сортів і ліній пшениці спельти. Проаналізовано від-мінності між якістю хліба з борош-на вищого сорту та обойного, показа-но актуальність диференційованого підходу до технологічних властивос-тей борошна для його виробництва. На основі досліджень фізико-хімічних, органолептичних показників хліба під-тверджено можливість перспективно-го використання зерна пшениці спельти в технології хлібопекарської продукції для розширен… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
7
0
2
Order By: Relevance
“…Results of plotting the function of desirability (add-in Experimental design (DOE) of Statistica 12 program) based on dependences (5) and (6) revealed that the highest yield of cereals (98.22 %) and the lowest yield of middling (1.77 %) can be obtained at the shortest duration of peeling (20 s) at steeping of grain for 120 minutes at its moisture content of 15.75 %.…”
Section: Results Of Studying the Influence Of Parameters Of Hydrothermentioning
confidence: 99%
See 1 more Smart Citation
“…Results of plotting the function of desirability (add-in Experimental design (DOE) of Statistica 12 program) based on dependences (5) and (6) revealed that the highest yield of cereals (98.22 %) and the lowest yield of middling (1.77 %) can be obtained at the shortest duration of peeling (20 s) at steeping of grain for 120 minutes at its moisture content of 15.75 %.…”
Section: Results Of Studying the Influence Of Parameters Of Hydrothermentioning
confidence: 99%
“…The extension of the range of finished products due to the use of raw materials of higher biological value, in particular, spelt wheat, deserve attention [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, given the modern laws of the market environment and the requirements for competitiveness of finished products, the results of the previous research [20,21] are not enough to form the optimum modes of processing spelt wheat grain. There is no relevant information in other papers [2,15,16]. That is why it was appropriate to conduct a comprehensive study of the influence of these parameters on the quantitative and qualitative indicators of milling production.…”
Section: Results Of Research Into the Influence Of Conditioning Parammentioning
confidence: 99%
“…Analysis of the information in literature [2,5,6,11] makes it possible to make the following conclusions. Spelt wheat grain, which has high biological value can effectively extend the assortment of bakery products and is competitive in today's market environment.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation